Patients' experiences of technology and care in adult intensive care. (13th April 2015) - Stayt, Louise Caroline; Seers, Kate; Tutton, Elizabeth
Abstract Aims To investigate patients' experiences of technology in an adult intensive care unit. Background Technology is fundamental to support physical recovery from critical illness in Intensive Care Units. As well as physical corollaries, psychological disturbances are reported in critically ill patients at all stages of their illness and recovery. Nurses play a key role in the physical and psychological care of patients;, however, there is a suggestion in the literature that the presence of technology may dehumanise patient care and distract the nurse from attending to patients psychosocial needs. Little attention has been paid to patients' perceptions of receiving care in a technological environment. Design This study was informed by Heideggerian phenomenology. Methods The research took place in 2009–2011 in a university hospital in England. Nineteen participants who had been patients in ICU were interviewed guided by an interview topic prompt list. Interviews were transcribed verbatim and analysed using Van Manen's framework. Findings Participants described technology and care as inseparable and presented their experiences as a unified encounter. The theme 'Getting on with it' described how participants endured technology by 'Being Good' and 'Being Invisible'. 'Getting over it' described why participants endured technology by 'Bowing to Authority' and viewing invasive technologies as a 'Necessary Evil'. Conclusion Patients experienced technology and care as a series of paradoxical relationships: alienating yet reassuring, uncomfortable yet comforting, impersonal yet personal. By maintaining a close and supportive presence and providing personal comfort and care nurses may minimize the invasive and isolating potential of technology.